The Impact of Emerging Countries on Sub-Saharan African Economies: Factors of Long-term Growth? - (:unkn) unknown (My University, 2013)
Panel 7.4: Global Economy and Development Cooperation in Emerging Countries and New Markets, http://www.cucstorino2013.it/en/programma/sessioni_parallele/attori_reti_e_processi_dello_sviluppo_economico/7_4_economia_globale_e_cooperazione_allo_sviluppo_nei_paesi_emergenti_e_nei_nuovi_mercati
Keywords: African Research